MORPHOLOGY OF DISTAL THIRD OF CLAVICLE IN DRY BONE AND CORRELATION WITH LENGTH: A CROSS-SECTIONAL STUDY. - Purohit, Dr . Kalpana; Yadav, Dr . Bharati; Purohit, Dr . Ankita (Student's Journal of Health Research Africa, 2024)
Background The human clavicle is the only transversely placed cancellous bone long bone of the body. The fracture of the distal end of the clavicle accounts for 12% to 15% of all fractured clavicles. Approximately 25% of distal clavicle fractures are unstable. This study aims to measure the dimensions and proportions of the distal third of the clavicle and correlate these measurements with the total length of the bone to aid in the development of better surgical interventions and prosthetics. Methods In this study, 40 left-side & 40 right-side human clavicles were included. The total length of the bone, the distance of the medial border of the conoid tubercle, and the center of the trapezoid tuberosity from the lateral edge of the clavicle were measured. Analysis of data was done by SPSS version 22 for Windows. Results The mean total length of right & left clavicle was125.5±11.9mm & 136.5±10.4mm. The mean length of the medial border of the conoid tubercle (CD) from the lateral edge was 43.0±7.3mm &43.5±4.9mm and the mean length of the center of the trapezoid tuberosity (TD) from the lateral edge was 18±4.1mm &18± 4.10mm of right & left clavicle respectively. The average of the mean of the proportion of the medial border conoid tubercle from the lateral edge of the clavicle & the total length of the clavicle was 0.33±0.045 & that of the center of the trapezoid tuberosity was 0.14±0.025. Conclusion The mean length of the left clavicle is more. The CD &TD will provide a guide for resection of the distal end of the clavicle in fracture and displacement of the acromioclavicular joint during repair. Recommendation Future research should involve larger, diverse samples to validate findings and refine surgical techniques, considering anatomical variations for improved patient outcomes.